Conserved developmental expression of Fezf in chordates and Drosophila and the origin of the Zona Limitans Intrathalamica (ZLI) brain organizer - Irimia, Manuel (BioMed Central, 2010)
BACKGROUND: The zona limitans intrathalamica (ZLI) and the isthmus organizer (IsO) are two major secondary organizers of vertebrate brain development. These organizers are located at the interface of the expression domains of key patterning genes (Fezf-Irx and Otx-Gbx, respectively). To gain insights into the evolutionary origin of the ZLI, we studied Fezf in bilaterians. RESULTS: In this paper, we identified a conserved sequence motif (Fezf box) in all bilaterians. We report the expression pattern of Fezf in amphioxus and Drosophila and compare it with those of Gbx, Otx and Irx. We found that the relative expression patterns of these genes in vertebrates are fully conserved in amphioxus and flies, indicating that the genetic subdivisions defining the location of both secondary organizers in early vertebrate brain development were probably present in the last common ancestor of extant bilaterians. However, in contrast to vertebrates, we found that Irx-defective flies do not show an affected Fezf expression pattern. CONCLUSIONS: The absence of expression of the corresponding morphogens from cells at these conserved genetic boundaries in invertebrates suggests that the organizing properties might have evolved specifically in the vertebrate lineage by the recruitment of key morphogens to these conserved genetic locations.